PERANAN BUDAYA SEKOLAH DALAM MEMBANGUN KARAKTER RELIGIUS - Imamudin Imamudin; Destri Astrianingsih; Siska Resti Maysara (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
Religious character is currently one of the most important characters possessed by students as a provision to live their lives. The weakness of character education that causes a character crisis in the world of education in Indonesia is currently a serious challenge for educators, especially the character of students representing the quality of education in schools. Strengthening a character is formed from a reflection of the culture in the school. Using the literature study method in data collection, this study will describe how school culture can build students' religious character. The findings from the study of various literatures show that school culture which consists of regular activities and daily habits involving all school members plays a role in the formation of religious character